Neuronal, affective, and sensory correlates of targeted helping behavior in male and female Sprague Dawley rats - Cox, Stewart S.; Brown, Brogan J.; Wood, Samuel K.; Brown, Samantha J.; Kearns, Angela M.; Reichel, Carmela M. (Frontiers in Behavioral Neuroscience, 2024)
Empathic behaviors are driven by the ability to understand the emotional states of others along with the motivation to improve it. Evidence points towards forms of empathy, like targeted helping, in many species including rats. There are several variables that may modulate targeted helping, including sex, sensory modalities, and activity of multiple neural substrates. Using a model of social contact-independent targeted helping, we first tested whether sex differences exist in helping behavior. Next, we explored sex differences in sensory and affective signaling, including direct visualization and an analysis of ultrasonic vocalizations made between animal pairs. Finally, we examined the neural activity in males and females of multiple regions of interest across time. Here, we aim to examine any behavioral differences in our lab's social contact independent targeted helping task between males and females. These findings are the first to intimate that, like other prosocial behaviors, males and females may exhibit similar social-independent targeted helping behavior, but the underlying sensory communication in males and females may differ. In addition, this is the first set of experiments that explore the neural correlates of social-independent targeted helping in both males and females. These results lay the groundwork for future studies to explore the similarities and differences that drive targeted helping in both sexes.